Jamie Oliver's food escapes : over 100 recipes from the great food regions of the world - Oliver, Jamie, 1975-; Loftus, David (New York : Hyperion, 2011)
Taking readers on a culinary adventure around the world, the chef features recipes from six of his favorite countries, including Spain, Morocco, and Sweden, that are authentic and infused with incredible flavor.
Spain -- Italy -- Sweden -- Morocco -- Greece -- France.
Includes an index.
Keywords: International cooking; Cooking, Spanish; Cooking, Italian; Cooking, Swedish; Cooking, Moroccan; Cooking, Greek; Cooking, French